1994
DOI: 10.3109/00498259409043226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green and black tea on hepatic xenobiotic metabolizing systems in the male F344 rat

Abstract: 1. The induction of phase I and II enzymes in the liver of the male F344 rat drinking 2% (w/v) solutions of green or black tea for 6 weeks was investigated. Also studied were glutathione (GSH) and cyst(e)ine in blood, liver and kidney, as well as serum cholesterol, HDL cholesterol, triglycerides, and total and free testosterone. 2. The total carbon monoxide-discernible liver P450, b5 and NADPH-cytochrome c(P450) reductase activities were similar in all groups. 3. There were significant increases in liver of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
2
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(74 citation statements)
references
References 22 publications
5
65
2
2
Order By: Relevance
“…UGT microsomal activity has been enhanced by chronic treatment with green tea beverages or extracts to a variable degree in animal studies (Sohn et al, 1994;Bu-Abbas et al, 1998;Zhu et al, 1998;Embola et al, 2002). Concerning the P450 enzymes, the data are discordant.…”
mentioning
confidence: 57%
“…UGT microsomal activity has been enhanced by chronic treatment with green tea beverages or extracts to a variable degree in animal studies (Sohn et al, 1994;Bu-Abbas et al, 1998;Zhu et al, 1998;Embola et al, 2002). Concerning the P450 enzymes, the data are discordant.…”
mentioning
confidence: 57%
“…Induction of these enzymes by either naturally occurring or synthetic agents represents a promising chemopreventive strategy (5)(6)(7)(8). Green tea or green tea polyphenols have been shown to modulate various xenobiotic metabolizing enzymes, including GSTs, in animal studies and in in vitro systems (9)(10)(11)(12)(13)(14). Phase II enzyme induction by green tea polyphenols is generally believed to involve the activation of the mitogenactivated protein kinase pathway via the electrophilicmediated stress response, resulting in the activation of transcription factors that bind to antioxidant/electrophile response element located on many phase II genes (15).…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al 46) have reported that the pretreatment of rats with 0.5% green tea in their drinking water for 2 or 4 weeks did not produce a significant increase in cytochrome P450 content but enhanced microsome-mediated formation of non-toxic hydroxylated metabolites of AFB 1 by 2-3 fold. It has also been reported by Sohn et al 47) and Bu-Abbas et al 48) that rats administered GTE for 4 or 6 weeks displayed no significant increase in total cytochrome P450 content in the liver but did display a significant increase in O-dealkylase activity of ethoxyresorufin (CYP1A1), methoxyresorufin (CYP1A2) and pentoxyresorufin (CYP2B1). Table 2 indicates the suppressive effect of individual GTP on AFB 1 -induced CA.…”
Section: Discussionmentioning
confidence: 82%